Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Beyond macrophages: FIPV tropism includes T and B lymphocytes - Aadhavan Balakumar; Patrawin Wanakumjorn; Kazuto Kimura; Ehren McLarty; Katherine Farrell; Terza Brostoff; Jully Pires; Tamar Cohen-Davidyan; Jennifer M. Cassano; Brian Murphy; Krystle Reagan; Amir Kol (Veterinary Microbiology, 2026)

Recent Chemo-morphological coma evolution of comet 67P/Churyumov–Gerasimenko - Brian P. Murphy; Cyrielle Opitom; Colin Snodgrass; Sophie E. Deam; Léa Ferellec; Matthew Knight; Vincent Okoth; Bin Yang (Planetary and Space Science, 2025)

Antibiotic discovery from a bacterial colony: isolation of new peptidic antibiotics using robotics, 3D printed bioassays, and MS-based bioinformatics - Jung-Ho Lee; Jin Yi Tan; Rui Ma; Linh Nguyen; Shahebraj Kahn; Mallique Qader; Enock Mpofu; Gauri Shetye; Nyssa K. Krull; Mario Augustinović; Sesselja Omarsdottir; William Edmonson; et al. (Phytochemistry Letters, 2025)

Evaluating the effectiveness of field-based probiotic treatments for stony coral tissue loss disease in southeast Florida, USA - Kelly A. Pitts; Mackenzie Scheuermann; Jonathan S. Lefcheck; Blake Ushijima; Natalie Danek; E. Murphy McDonald; Aaron R. Milanese; Monica D. Schul; Julie L. Meyer; Kathryn A. Toth; Zachary Ferris; Yesmarie T. De La Flor; et al. (Frontiers in Marine Science, 2025)
Stony coral tissue loss disease (SCTLD) has spread throughout Florida’s Coral Reef, causing extensive mortality of over 30 species of reef-building corals, and has rapidly spread to many other countries and territories throughout the Caribbean. Current treatments for SCTLD, including a proprietary paste mixed with the antibiotic amoxicillin, do not provide protection from future infections and may select for antibiotic-resistant pathogenic bacteria. In contrast, beneficial microorganisms (i.e., probiotics), may directly treat or act as prophylactics for corals exposed to SCTLD. This study investigated the use of the bacterium Pseudoalteromonas sp. McH1-7, previously isolated from a SCTLD-resistant fragment of Montastraea cavernosa , as a potential probiotic treatment for SCTLD-infected M. cavernosa colonies in the wild. We developed and tested two probiotic deployment methods: (1) the injection of a probiotic in seawater suspension into a weighted bag placed over the coral to treat the whole colony; and (2) a sodium alginate-based paste that was applied directly to each disease lesion. After treatment, the disease progression of each colony was routinely monitored using three-dimensional photogrammetry for 2.5 years. Slurries of tissue and mucus samples were taken from healthy and diseased colonies before treatment, two weeks after treatment, and three months after treatment to identify possible shifts in bacterial and archaeal communities. McH1–7 successfully slowed SCTLD lesion progression for 2.5 years following treatments when delivered using the whole-colony treatment technique. Our assessment of the microbiome following treatment showed that McH1–7 was effective without dominating bacterial communities among infected corals. In contrast, corals treated with the probiotic paste lost more tissue than corals treated with the control paste, indicating that the lesion-specific probiotic paste is not effective at stopping SCTLD. Probiotic inoculations via a whole-colony treatment technique may provide a path toward slowing the loss of reef-building corals due to SCTLD.

A review of post-wildfire adaptations of surface-water-quality models: Synthesis, gaps, and opportunities - Zachary M. Shephard; Trevor F. Partridge; Sheila F. Murphy; Michelle A. Walvoord; Brian A. Ebel (Science of The Total Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Amyloid-producing ameloblastoma of the maxilla in a 17-year-old cynomolgus macaque (Macaca fascicularis) - Caitlin M. Culligan; Brian G. Murphy; Andrew N. Cartoceti; Elise E.B. LaDouceur (Journal of Comparative Pathology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Stability of Protein Pharmaceuticals: Recent Advances - Mark Cornell Manning; Ryan E. Holcomb; Robert W. Payne; Joshua M. Stillahn; Brian D. Connolly; Derrick S. Katayama; Hongcheng Liu; James E. Matsuura; Brian M. Murphy; Charles S. Henry; Daan J. A. Crommelin (Pharmaceutical Research, 2024)

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

Pyrolysis, a recovery solution to reduce landfilling of residual organic waste generated from mixed municipal waste - Jessica Graça; Marzena Kwapinska; Brian Murphy; Tim Duggan; James J. Leahy; Brian Kelleher (Environmental Science and Pollution Research, 2024)
Despite policies to restrict the mixing of organic waste with other general waste and improve its separation at source, municipal solid waste still contains a high proportion of organic waste. The residual organic waste is generated as a by-product of the mechanical treatment of municipal solid waste (MSW) and is mainly disposed in landfills after composting. Its reuse and recovery status varies across European countries. Most countries restrict the use of biostabilised residual waste (BSRW) to landfill cover, whereas others have regulated it as marketable compost. Crucially, BSRW is set to lose its “recycled” status under the revised European Union waste framework, with probably tighter restrictions and increased costs imposed for the landfilling of organic waste. Our research aimed to investigate pyrolysis as an alternative technology to treat the 10–40 mm fraction of BSRW (representing 50% of BSRW generated). Pyrolysis at 700 °C was carried out and feedstock and pyrolysis products were characterized. Mass and energy balances showed that pyrolysis produced hot vapour/gas whose combustion may render the pyrolysis process energetically sustainable. Biochar comprises 30–50% of BRSW mass after removal of glass, metal and stones. Our results indicate that pyrolysis has the potential to create options for contributing to reduce the landfilling of BSRW; however, the presence of residual impurities may limit biochar applications.

Economic potential of agricultural-riparian shrub willow: An evaluation of the biomass producing capabilities and costs of cultivating Salix viminalis downslope of potato cropping systems in PEI - Holly D.M. Wilts; David L. Burton; Aitazaz A. Farooque; William R. Schroeder; Brian Murray; Emily K. Murphy; Matthew Ramsay (Biomass and Bioenergy, 2024)

A subset of equine oral squamous cell carcinomas is associated with Equus caballus papillomavirus 2 infection - Jennifer Luff; Shaina Weingart; Susan May; Brian Murphy (Journal of Comparative Pathology, 2023)

Exploring metapopulation‐scale suppression alternatives for a global invader in a river network experiencing climate change - Brian D. Healy; Phaedra Budy; Charles. B. Yackulic; Brendan P. Murphy; Robert C. Schelly; Mark C. McKinstry (Conservation Biology, 2023)
Invasive species can dramatically alter ecosystems, but eradication is difficult, and suppression is expensive once they are established. Uncertainties in the potential for expansion and impacts by an invader can lead to delayed and inadequate suppression, allowing for establishment. Metapopulation viability models can aid in planning strategies to improve responses to invaders and lessen invasive species’ impacts, which may be particularly important under climate change. We used a spatially explicit metapopulation viability model to explore suppression strategies for ecologically damaging invasive brown trout ( Salmo trutta ), established in the Colorado River and a tributary in Grand Canyon National Park. Our goals were to estimate the effectiveness of strategies targeting different life stages and subpopulations within a metapopulation; quantify the effectiveness of a rapid response to a new invasion relative to delaying action until establishment; and estimate whether future hydrology and temperature regimes related to climate change and reservoir management affect metapopulation viability and alter the optimal management response. Our models included scenarios targeting different life stages with spatially varying intensities of electrofishing, redd destruction, incentivized angler harvest, piscicides, and a weir. Quasi‐extinction (QE) was obtainable only with metapopulation‐wide suppression targeting multiple life stages. Brown trout population growth rates were most sensitive to changes in age 0 and large adult mortality. The duration of suppression needed to reach QE for a large established subpopulation was 12 years compared with 4 with a rapid response to a new invasion. Isolated subpopulations were vulnerable to suppression; however, connected tributary subpopulations enhanced metapopulation persistence by serving as climate refuges. Water shortages driving changes in reservoir storage and subsequent warming would cause brown trout declines, but metapopulation QE was achieved only through refocusing and increasing suppression. Our modeling approach improves understanding of invasive brown trout metapopulation dynamics, which could lead to more focused and effective invasive species suppression strategies and, ultimately, maintenance of populations of endemic fishes.

Use of Enrofloxacin and Hydrotherapy in the Management of Fibrodysplasia Ossificans Progressiva (FOP) in a Savannah Cat - Kim L. Jacobsen; Valerie Wiebe; Autumn P. Davidson; Brian G. Murphy; Jr. Roy R. Pool (Topics in Companion Animal Medicine, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Profiling of Fusarium head blight resistance QTL haplotypes through molecular markers, genotyping-by-sequencing, and machine learning - Zachary J. Winn; Jeanette Lyerly; Brian Ward; Gina Brown-Guedira; Richard E. Boyles; Mohamed Mergoum; Jerry Johnson; Stephen Harrison; Ali Babar; Richard E. Mason; Russell Sutton; J. Paul Murphy (Theoretical and Applied Genetics, 2022)

Effects of modafinil on electroencephalographic microstates in healthy adults - Samantha R. Linton; Michael Murphy; Hans S. Schroder; Micah Breiger; Ann M. Iturra-Mena; Brian D. Kangas; Jack Bergman; William A. Carlezon; Victoria B. Risbrough; Samuel A. Barnes; Andre Der-Avakian; Diego A. Pizzagalli (Psychopharmacology, 2022)

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

Effect of surfactant concentration and sterilization process on intraocular pressure–lowering activity of Δ9-tetrahydrocannabinol-valine-hemisuccinate (NB1111) nanoemulsions - Corinne Sweeney; Narendar Dudhipala; Ruchi Thakkar; Tabish Mehraj; Sushrut Marathe; Waseem Gul; Mahmoud. A. ElSohly; Brian Murphy; Soumyajit Majumdar (Drug Delivery and Translational Research, 2021)

Sediment Deposition Following Construction of a Breakwater Harbor: Point Judith Harbor of Refuge, Rhode Island, USA - Bryan A. Oakley; Cody J. Murphy; Kym K. Lee; Robert J. Hollis; Brian Caccioppoli; John W. King (Journal of Marine Science and Engineering, 2020)
Breakwaters are a common shoreline protection structure, often trapping sediment as the incoming wave energy is reduced. Quantifying the dynamics and volume of these sediment sinks within a coastal system is an important step toward understanding the sediment budget for a particular coastal area. This study examines the volume of sediment deposited within the breakwater enclosed Point Judith Harbor of Refuge (Rhode Island, United States of America (USA)) in the late 19th century using seismic reflection profiles, bathymetric mapping, and isotopic analysis of core sediment. Geophysical profiles show a district seismic facies up to 4 m thick above the ravinement surface, particularly in the western and central portion of the harbor. Century-scale bathymetric changes revealed shoaling of a similar magnitude, and isotopic data support the deposition of this sediment package within the 20th century. The total volume of sediment within the harbor exceeds 5.0 × 106 m3, with an estimated sand volume of 3.6 × 106 m3. The results show that the harbor is a substantial sediment sink for the Rhode Island South Shore and provide the basis for future studies of the sediment budget for this shoreline.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Adaptable Monitoring Package Development and Deployment: Lessons Learned for Integrated Instrumentation at Marine Energy Sites - Brian Polagye; James Joslin; Paul Murphy; Emma Cotter; Mitchell Scott; Paul Gibbs; Christopher Bassett; Andrew Stewart (Journal of Marine Science and Engineering, 2020)
Integrated instrumentation packages are an attractive option for environmental and ecological monitoring at marine energy sites, as they can support a range of sensors in a form factor compact enough for the operational constraints posed by energetic waves and currents. Here we present details of the architecture and performance for one such system—the Adaptable Monitoring Package—which supports active acoustic, passive acoustic, and optical sensing to quantify the physical environment and animal presence at marine energy sites. we describe cabled and autonomous deployments and contrast the relatively limited system capabilities in an autonomous operating mode with more expansive capabilities, including real-time data processing, afforded by shore power or in situ power harvesting from waves. Across these deployments, we describe sensor performance, outcomes for biological target classification algorithms using data from multibeam sonars and optical cameras, and the effectiveness of measures to limit biofouling and corrosion. On the basis of these experiences, we discuss the demonstrated requirements for integrated instrumentation, possible operational concepts for monitoring the environmental and ecological effects of marine energy converters using such systems, and the engineering trade-offs inherent in their development. Overall, we find that integrated instrumentation can provide powerful capabilities for observing rare events, managing the volume of data collected, and mitigating potential bias to marine animal behavior. These capabilities may be as relevant to the broader oceanographic community as they are to the emerging marine energy sector.

Exploring and interpreting spatiotemporal interactions between native and invasive carnivores across a gradient of rainforest degradation - Zach J. Farris; Brian D. Gerber; Sarah Karpanty; Asia Murphy; Erin Wampole; Felix Ratelolahy; Marcella J. Kelly (Biological Invasions, 2020)

Movement, habitat use, and survival of juvenile grass carp in an Appalachian reservoir - Matthew A. Weberg; Brian R. Murphy; John R. Copeland; Andrew L. Rypel (Environmental Biology of Fishes, 2020)

No environmental context-dependent effect, but interference, of physical activity on object location memory - Alexandra G. Hammond; Erin M. Murphy; Brian M. Silverman; Ronan S. Bernas; Daniele Nardi (Cognitive Processing, 2019)

Denaturation and Aggregation of Interferon-τ in Aqueous Solution - Ryan R. Manning; Glenn A. Wilson; Ryan E. Holcomb; Nathaniel J. Zbacnik; Auria A. Tellechea; Chelsey L. Gilley-Dunn; Ryan J. Krammes; Nathan S. Krammes; Gabriel J. Evans; Charles S. Henry; Mark Cornell Manning; Brian M. Murphy; et al. (Pharmaceutical Research, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Impairment in Mismatch Negativity but not Repetition Suppression in Schizophrenia - Brian A. Coffman; Sarah M. Haigh; Tim K. Murphy; Dean F. Salisbury (Brain Topography, 2017)

A seed dressing combining fungal endophyte spores and fungicides improves seedling survival and early growth in barley and oat - Brian R. Murphy; Fiona M. Doohan; Trevor R. Hodkinson (Symbiosis, 2017)

Pilot Trial of Intravenous Lipid Emulsion Treatment for Severe Nifedipine-Induced Shock - Christine M. Murphy; Cliff Williams; Michael E. Quinn; Brian Nicholson; Thomas Shoe; Michael C. Beuhler; William P. Kerns (Journal of Medical Toxicology, 2016)

Impact of including land-use change emissions from biofuels on meeting GHG emissions reduction targets: the example of Ireland - Magdalena M. Czyrnek-Delêtre; Alessandro Chiodi; Jerry D. Murphy; Brian P. Ó Gallachóir (Clean Technologies and Environmental Policy, 2016)

Farm gate level nitrogen balance and use efficiency changes post implementation of the EU Nitrates Directive - Cathal Buckley; David P. Wall; Brian Moran; Stephen O’Neill; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2016)

Potential effects of dam cascade on fish: lessons from the Yangtze River - Fei Cheng; Wei Li; Leandro Castello; Brian R. Murphy; Songguang Xie (Reviews in Fish Biology and Fisheries, 2015)

Population genetic structure and its implication for conservation of Coreius guichenoti in the upper Yangtze River - Fei Cheng; Wei Li; Michelle Klopfer; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2015)

Developing the EU Farm Accountancy Data Network to derive indicators around the sustainable use of nitrogen and phosphorus at farm level - Cathal Buckley; David P. Wall; Brian Moran; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2015)

Persistent fungal root endophytes isolated from a wild barley species suppress seed-borne infections in a barley cultivar - Brian R. Murphy; Fiona M. Doohan; Trevor R. Hodkinson (BioControl, 2015)

Fungal root endophytes of a wild barley species increase yield in a nutrient-stressed barley cultivar - Brian R. Murphy; Fiona M. Doohan; Trevor R. Hodkinson (Symbiosis, 2015)

Molecular heterogeneity of familial myeloproliferative neoplasms revealed by analysis of the commonly acquired JAK2, CALR and MPL mutations - Stephen E. Langabeer; Karl Haslam; Jennifer Linders; Melanie J. Percy; Eibhlin Conneally; Amjad Hayat; Brian Hennessy; Maeve Leahy; Karen Murphy; Margaret Murray; Fionnuala Ni Ainle; Patrick Thornton; et al. (Familial Cancer, 2014)

Sagittal otolith microstructure, early growth and development of Coilia ectenes in the Yangtze Estuary, China - Yanfei Huang; Fei Cheng; Brian R. Murphy; Songguang Xie (Fisheries Science, 2014)

Temporal change in the herbaceous understory community of an old-growth forest: from seasons to decades - Stephen J. Murphy; Brian C. McCarthy (Plant Ecology, 2014)

Yield increase induced by the fungal root endophyte Piriformospora indica in barley grown at low temperature is nutrient limited - Brian R. Murphy; Fiona M. Doohan; Trevor R. Hodkinson (Symbiosis, 2014)

Reduced growth and reproductive investment of Hemiculter leucisculus (Cyprinidae) in a reservoir with introduced icefish Neosalanx taihuensis (Salangidae) - Xinglu Wang; Jianguo Xiang; Jiashou Liu; Ming Liu; Lang Wu; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2013)

Virus species polemics: 14 senior virologists oppose a proposed change to the ICTV definition of virus species - Marc H. V. Van Regenmortel; Hans-Wolfgang Ackermann; Charles H. Calisher; Ralf G. Dietzgen; Marian C. Horzinek; Gunther M. Keil; Brian W. J. Mahy; Giovanni P. Martelli; Frederick A. Murphy; Craig Pringle; Bert K. Rima; Tim Skern; et al. (Archives of Virology, 2013)

Evidence of yellow perch, largemouth bass and pumpkinseed metapopulations in coastal embayments of Lake Ontario - Shidan Murphy; Nick C. Collins; Susan E. Doka; Brian J. Fryer (Environmental Biology of Fishes, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Preliminary evidence of delayed spawning and suppressed larval growth and condition of the major carps in the Yangtze River below the Three Gorges Dam - Guo Zhang; Lang Wu; Hongtao Li; Ming Liu; Fei Cheng; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2012)

Polyandry and multiple paternities in the threatened Agassiz’s desert tortoise, Gopherus agassizii - Christina M. Davy; Taylor Edwards; Amy Lathrop; Mark Bratton; Mark Hagan; Brian Henen; Kenneth A. Nagy; Jonathon Stone; L. Scott Hillard; Robert W. Murphy (Conservation Genetics, 2011)

Impacts of hatchery release on genetic structure of rock carp Procypris rabaudi in the upper Yangtze River, China - Fei Cheng; Qingjiang Wu; Ming Liu; K. V. Radhakrishnan; Brian R. Murphy; Songguang Xie (Fisheries Science, 2011)

Identification of individuals born in different spawning seasons using otolith microstructure to reveal life history of Neosalanx taihuensis - Lang Wu; Jia Shou Liu; Xing Lu Wang; Guo Zhang; Zheng You Zhang; Brian R. Murphy; Song Guang Xie (Fisheries Science, 2011)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

Otolith retrieval from faeces and reconstruction of prey-fish size for Great Cormorant (Phalacrocorax carbo) wintering at the East Dongting Lake National Nature Reserve, China - K. V. Radhakrishnan; Ming Liu; Wenping He; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2010)

George Martin Baer (1936–2009): in memoriam - Frederick A. Murphy; Charles E. Rupprecht; Brian W. J. Mahy; Leland E. Carmichael (Archives of Virology, 2010)

Effects of acute tryptophan depletion on neural processing of facial expressions of emotion in humans - Eileen Daly; Quinton Deeley; Brian Hallahan; Michael Craig; Michael Brammer; Melissa Lamar; Anthony Cleare; Vincent Giampietro; Christine Ecker; Lisa Page; Fiona Toal; Mary L. Phillips; et al. (Psychopharmacology, 2010)

Maternal influences on population dynamics: evidence from an exploited freshwater fish - Paul A. Venturelli; Cheryl A. Murphy; Brian J. Shuter; Thomas A. Johnston; Peter J. van Coeverden de Groot; Peter T. Boag; John M. Casselman; Robert Montgomerie; Murray D. Wiegand; William C. Leggett (Ecology, 2010)
We used a field experiment, population modeling, and an analysis of 30 years of data from walleye ( Sander vitreus ; a freshwater fish) in Lake Erie to show that maternal influences on offspring survival can affect population dynamics. We first demonstrate experimentally that the survival of juvenile walleye increases with egg size (and, to a lesser degree, female energy reserves). Because egg size in this species tends to increase with maternal age, we then model these maternal influences on offspring survival as a function of maternal age to show that adult age structure can affect the maximum rate at which a population can produce new adults. Consistent with this hypothesis, we present empirical evidence that the maximum reproductive rate of an exploited population of walleye was approximately twice as high when older females were abundant as compared to when they were relatively scarce. Taken together, these results indicate that age‐ or size‐based maternal influences on offspring survival can be an important mechanism driving population dynamics and that exploited populations could benefit from management strategies that protect, rather than target, reproductively valuable individuals.

Stability of Protein Pharmaceuticals: An Update - Mark Cornell Manning; Danny K. Chou; Brian M. Murphy; Robert W. Payne; Derrick S. Katayama (Pharmaceutical Research, 2010)

Two spawning stocks of icefish Neosalanx taihuensis revealed from annual reproductive cycle analyses - Wang Bao Gong; Hong Tao Li; Shou Qi Xie; Jia Shou Liu; Brian R. Murphy; Song Guang Xie (Fisheries Science, 2009)

Glycemic index, carbohydrate and fiber intakes and risk of reflux esophagitis, Barrett’s esophagus, and esophageal adenocarcinoma - Helen G. Mulholland; Marie M. Cantwell; Lesley A. Anderson; Brian T. Johnston; R. G. Peter Watson; Seamus J. Murphy; Heather R. Ferguson; Jim McGuigan; John V. Reynolds; Harry Comber; Liam J. Murray (Cancer Causes & Control, 2009)

Circulating fatty acids and prostate cancer risk in a nested case–control study: the Multiethnic Cohort - Song-Yi Park; Lynne R. Wilkens; Susanne M. Henning; Loïc Le Marchand; Kun Gao; Marc T. Goodman; Suzanne P. Murphy; Brian E. Henderson; Laurence N. Kolonel (Cancer Causes & Control, 2009)

Antiproliferative compounds of Artabotrys madagascariensis from the Madagascar rainforest - Brian T. Murphy; Shugeng Cao; Peggy J. Brodie; James S. Miller; Fidy Ratovoson; Chris Birkinshaw; Etienne Rakotobe; Vincent E. Rasamison; Karen Tendyke; Edward M. Suh; David G. I. Kingston (Natural Product Research, 2008)

Tilapia (Teleostei: Cichlidae) status in Nicaraguan natural waters - Jeffrey K. McCrary; Brian R. Murphy; Jay R. Stauffer; Stuart S. Hendrix (Environmental Biology of Fishes, 2007)

Dietary fiber and colorectal cancer risk: the multiethnic cohort study - Abraham M. Y. Nomura; Jean H. Hankin; Brian E. Henderson; Lynne R. Wilkens; Suzanne P. Murphy; Malcolm C. Pike; Loic Le Marchand; Daniel O. Stram; Kristine R. Monroe; Laurence N. Kolonel (Cancer Causes & Control, 2007)

The New River, Virginia, muskellunge fishery: population dynamics, harvest regulation modeling, and angler attitudes - Travis O. Brenden; Eric M. Hallerman; Brian R. Murphy; John R. Copeland; Joseph A. Williams (Environmental Biology of Fishes, 2007)

Body mass index and physical activity as risk factors for pancreatic cancer: the Multiethnic Cohort Study - Ute Nöthlings; Lynne R. Wilkens; Suzanne P. Murphy; Jean H. Hankin; Brian E. Henderson; Laurence N. Kolonel (Cancer Causes & Control, 2007)

Tilapia (Teleostei: Cichlidae) status in Nicaraguan natural waters - Jeffrey K. McCrary; Brian R. Murphy; Jay R. Stauffer; Sherman S. Hendrix (Environmental Biology of Fishes, 2007)

Gene expression analysis in a canine model of X-linked Alport syndrome - Kimberly A. Greer; Marnie A. Higgins; Melissa L. Cox; Timothy P. Ryan; Brian R. Berridge; Clifford E. Kashtan; George E. Lees; Keith E. Murphy (Mammalian Genome, 2006)

Distribution, Feeding and Body Condition of Four Small Fish Species in the Near-shore and Central Areas of Liangzi Lake, China - Songguang Xie; Zhongjie Li; Yibo Cui; Brian R. Murphy (Environmental Biology of Fishes, 2005)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Sequence Analysis of the Washington/1964 Strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild-Type Recombinant HPIV1 Produced by Reverse Genetics - Jason T. Newman; Sonja R. Surman; Jeffrey M. Riggs; Chris T. Hansen; Peter L. Collins; Brian R. Murphy; Mario H. Skiadopoulos (Virus Genes, 2002)

Obituary - Frederick A. Murphy; Charles H. Calisher; Brian W. J. Mahy; Pertti Arstila (Archives of Virology, 2001)

Sequence Determination and Molecular Analysis of Two Strains of Bovine Parainfluenza Virus Type 3 that are Attenuated for Primates - Jane E. Bailly; Josephine M. Mcauliffe; Mario H. Skiadopoulos; Peter L. Collins; Brian R. Murphy (Virus Genes, 2000)

Pathogenesis of Cryptococcus neoformans is Associated with Quantitative Differences in Multiple Virulence Factors - Rebecca Blackstock; Kent L. Buchanan; Robert Cherniak; Thomas G. Mitchell; Brian Wong; Ann Bartiss; Lydgia Jackson; Juneann W. Murphy (Mycopathologia, 1999)

In Memoriam Helio Gelli Pereira (1918–1994) - Brian Mahy; Fred Murphy (Archives of Virology, 1994)

Association Business - David Curwen; Ronald Knight; Therese M. Work; Hugh J. Murphy; Pete Weingartner; John Ojala; Gary Franc; Roger Brook; Tom German; Sam Thorton; John Bamberg; John C. Wallace; et al. (American Journal of Potato Research, 1993)